Macroscopic perspective on phase transition behavior of natural single-crystal graphite under different pressure environments - Xiaoshuang Yin; Songyang Li; Lijuan Wang; Peiyuan Liu; Zhihai Cheng; Huiyang Gou; Liuxiang Yang (Matter and Radiation at Extremes)
Comprehensive understanding of the direct transformation pathway from graphite to diamond under high temperature and high pressure has long been one of the fundamental goals in materials science. Despite considerable experimental and theoretical progress, current experimental studies have mainly focused on the local microstructural characterizations of recovered samples, which has certain limitations for high-temperature and high-pressure products, which often exhibit diversity. Here, we report on the pressure-induced phase transition behavior of natural single-crystal graphite under three distinct pressure-transmitting media from a macroscopic perspective using in situ two-dimensional Raman spectroscopy, scanning electron microscopy, and atomic force microscopy. The surface evolution process of graphite before and after the phase transition is captured, revealing that pressure-induced surface textures can impede the continuity of the phase transition process across the entire single crystal. Our results provide a fresh perspective for studying the phase transition behavior of graphite and greatly deepen our understanding of this behavior, which will be helpful in guiding further high-temperature and high-pressure syntheses of carbon allotropes.